Inpatient Care of Community-Acquired Pneumonia: The Effect of Antimicrobial Guidelines on Clinical Outcomes and Drug Costs in Canadian Teaching Hospitals - Theodore K Marras; Linda Jamieson; Charles K Chan (Canadian Respiratory Journal)
BACKGROUND: Evidence supporting antibiotic treatment guidelines and respiratory quinolones (RQs) in community-acquired pneumonia (CAP) is limited.